Pendekatan Tekno-Ekonomi untuk Pengembangan Sistem Energi Hibrida Hidro-Biomassa untuk Pasokan Listrik Berkelanjutan di Daerah Pedesaan - Muljono, Agung Budi; Poetra, Satrya Bhayangkara; Parhan, Lukman (Depertment of Electrical Engineering University of Mataram, 2025)
Indonesia is one of the countries crossed by the equator, so it has quite large renewable energy potential, including in the Lombok area. Therefore, the use of renewable energy-based power plants can be applied throughout Indonesia. Lombok Island with its geographical conditions in the form of an archipelago with plains from the coast to the mountains has great potential for energy ranging from wind, water, biomass and solar power. The purpose of this system planning is to determine the importance of alternative energy in providing electricity for rural communities to obtain a sustainable supply of electricity based on hydro and biomass energy through a techno-economic approach. This research was applied to rural communities in Pemenang, Lombok, as an energy community. The software used for this system planning is Homer 2.19. The optimization results obtained using Homer are using hydroelectric power plants, biogas energy, converters, and batteries so that the total funds needed to purchase system components when the project starts are US 116,200, the present value of the installation and operation costs of the system until the project is complete (NPC) is US 514,764, the average price per kWh of electricity generated is US 0.082.